2014
DOI: 10.7482/0003-9438-57-003
|View full text |Cite
|
Sign up to set email alerts
|

Glucose infusion response on some metabolic parameters in dairy cows during transition period

Abstract: Abstract. The aim of this study was to evaluate the effect of glucose tolerance test (GTT) on glucose, insulin, non-esterified fatty acids (NEFA) and β-Hydroxybutyrate (BHB) concentration in dairy cows during prepartum and postpartum period. Forty Two clinically healthy Holstein cows were enrolled in two high producing dairy farms in the Northeast Italy. All animals were divided into two equal groups on the basis of the farm of origin: Group A (farm located in Vicenza) and Group B (farm located in Padua). Body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 19 publications
5
44
0
Order By: Relevance
“…The decrease in insulin levels found during post-partum is consistent with previous studies which reported high insulin levels before parturition, followed by a gradual decrease from 10 days before parturition remaining relatively low throughout lactation [28]. Lower glucose and insulin levels found during the post-partum period relative to the pre-partum period may be due to a decreased responsiveness of pancreatic β-cells to a state of hyperglycemia, caused by factors which inhibit the release of insulin [7].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The decrease in insulin levels found during post-partum is consistent with previous studies which reported high insulin levels before parturition, followed by a gradual decrease from 10 days before parturition remaining relatively low throughout lactation [28]. Lower glucose and insulin levels found during the post-partum period relative to the pre-partum period may be due to a decreased responsiveness of pancreatic β-cells to a state of hyperglycemia, caused by factors which inhibit the release of insulin [7].…”
Section: Discussionsupporting
confidence: 81%
“…A similar decrease of urea and K and the increase of AST levels found at post-partum in this study have been previously described by Fiore et al [9]. The AST increase could be associated to disorders involving the liver, including ketosis, even at subclinical levels [35].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…There are several studies on metabolic profile during the periods of the productive life of the cows such as transition and lactation periods (Ghanem et al, 2012;Piccione et al, 2012;Fiore et al, 2014). Based on author's knowledge, there is little information regarding the circulating metabolic profile in different physiological states of dairy cows in a comprehensive study.…”
Section: Introductionmentioning
confidence: 99%